Embracing exile: the case for Jewish diaspora - Kraemer, David C. (Oxford scholarship online, 2025)
'Embracing Exile' analyzes biblical and rabbinic texts, philosophical treatises, studies of Kabbalah, Hasidism, and a multiplicity of modern expressions for a comprehensive history of Jewish responses to and justifications of their diasporas. It shows that Diaspora Jews through the ages insisted that God joined them in their exiles, that 'Zion' was found in Babylon and Eastern Europe, and that, as citizens of the world, Jews could only live throughout the world. The result is a convincing assertion that lament has not been the most common Jewish response to diaspora and that Zionism is not the natural outcome of either Jewish ideology or history.